Effect of aircraft deicer on deicer-scaling resistance and frost resistance of airport pavement concrete. (August 2020) - Lai, Y; Liu, Y; Wang, P; Ma, D X; Guo, B; Sun, K; Hou, S
Abstract: This paper studies the effect of aircraft deicer on deicer-scaling resistance and frost resistance of airport pavement concrete. The mass loss and surface profile of non-air-entrained and air-entrained concrete eroded by water and aircraft deicer are analysed. The surface profile, mass loss rate and relative dynamic elasticity modulus of air-entrained concrete eroded by water and 5% aircraft deicer are discussed during freeze-thaw cycles. It is shown that the low and medium concentration deicer has a negative effect on the deicer-scaling resistance of concrete, and 5% aircraft deicer has the greatest influence. Adding air-entraining agent can improve the deicer-scaling resistance of concrete. Compared with water, 5% aircraft deicer has a negative effect on the frost resistance of air-entrained concrete. The deicer-scaling resistance and frost resistance of air-entrained concrete meet requirements for airport pavement in the most severely cold regions in China.